Business, Labor and Political Efficiency: Post-World War II Municipal Reform in Eau Claire, Wisconsin - Triplett, Adam (My University, 2008)
For decades historians and political scientists alike have been studying the trends and processes of municipal level political reform within the United States. Their attention has largely focused on answering questions like what social forces, economic factors and political controversies have fueled political change. A great portion of the research on political change has focused on the reforms that occurred during the Progressive Era. It is only within the last few decades that scholars have begun to investigate the wave of municipal reforms that occurred in the years following the Second World War. However, the small body of scholarly research that has developed over the past few decades has largely ignored the reforms that took place within the state of Wisconsin. Through an examination and analysis Eau Claire, Wisconsin's movement to change its government in the late 1940's this paper will attempt to expand the existing scholarship on municipal political reform into an area of the United States.
Keywords: Municipal government--Reform; Municipal government--Wisconsin--Eau Claire; Eau Claire (Wis.)--Politics and government; Municipal government--History--20th century